PERANCANGAN RUMAH TINGGAL YANG MERESPON KONDISI PANDEMIK; PASSIVE DESIGN SEBAGAI UPAYA UNTUK MENYARING PATOGEN - Mubarrok, Noor Zakiy; Adityo, Adityo; Alfionita, Clarissa; Mulyadi, Event Alviando; Utaminingtyas, Brigita Murti (Jurnal Arsitektur ARCADE, 2022)
Abstract: Adaptation to the pandemic has been going on from past eras. An increasingly modern society learns a lot from the previous case in dealing with the next pandemic. Technological advances and new discoveries in various fields make it easy for humans to deal with existing conditions, both individually and systematically. But does it ever come to our thoughts if we are in the worst condition when we cannot rely on technology anymore, when all systems are shut down, when we are in such catastrophe, is there anything we can do? This design tries to find a solution by utilizing the existing natural potential and our adaptation as a human, wisely. Cyclical Design Process used in the design process, starting with analysis; both programmatic and site analysis, synthesis which consist of conceptual, zoning and the design implementation, and evaluation using the ENVI-met software to evaluate and also to prove the design. The result is a house with multi mass, which has different orientation, connected by the courtyard to maximize the daylight and natural ventilation inside the house, and also separating the activity of the inhabitant, to minimize the spread of the virus among the inhabitants. Vegetation chosen in this design for supporting the passive design system, as a pathogen trap and ensuring food sufficiency for inhabitants.Abstrak: Adaptasi terhadap pandemik telah berlangsung selama berabad-abad. Masyarakat modern mempelajari kasus yang terjadi sebelumnya guna menghadapi kondisi pandemik berikutnya. Kemajuan teknologi dan ilmu pengetahuan memberikan kemudahan bagi masyarakat untuk menghadapi kondisi yang ada, baik secara individu maupun sistemik. Permasalahan yang diangkat adalah bagaimana jika dalam kondisi terburuk, teknologi yang membantu dan memudahkan kita beradaptasi tidak dapat digunakan. Rancangan ini mencoba untuk mencari solusi dengan memanfaatkan potensi alam yang ada serta adaptasi kita sebagai manusia dengan bijak. Metode Cyclical Design Process digunakan dalam proses perancangan, diawali dengan analisis programatik dan analisis tapak, sintesis yang meliputi konsep, zonasi dan implementasi desain serta evaluasi terhadap rancangan dengan menggunakan software ENVI-met untuk pembuktian rancangan. Hasilnya sebuah rancangan rumah tinggal multi massa dengan orientasi massa yang berbeda, dihubungkan dengan taman di tengah massa bangunan guna memaksimalkan pencahayaan dan penghawaan alami dalam ruang, sekaligus memecah aktivitas guna meminimalkan penyebaran virus diantara penghuni. Penggunaan vegetasi dalam perancangan selain untuk memaksimalkan sistem desain pasif, penyaring patogen serta memenuhi kebutuhan pangan mandiri bagi penghuni.